Do International Students Speak Confidently? Exploring English-Speaking Anxiety Among Thai and Egyptian Students - Danisti, Velia; Masita, Ella; Yulia, Yulia (International Journal of Language Teaching and Education, 2025)
This study investigates English-speaking anxiety among international students at Jambi University, focusing on two individuals from Thailand and Egypt. Despite assumptions that international students possess high English proficiency, many still experience anxiety, especially in academic and cross-cultural settings. Using a qualitative case study approach, data were collected through semi-structured interviews and analyzed using thematic analysis. Findings revealed stark contrasts: the Thai participant demonstrated high anxiety, primarily due to fear of negative evaluation, limited prior exposure to English, and high academic expectations. Meanwhile, the Egyptian participant exhibited low anxiety, citing early English education and cultural adaptability as key factors. Both participants utilized coping strategies such as preparation, peer support, and relaxation techniques. The study confirms that speaking anxiety is influenced not only by language ability but also by psychological, social, and cultural dynamics. These insights are essential for educators and institutions to create inclusive environments that support international students' emotional and academic success.